F-spondin negatively regulates dental follicle differentiation through the inhibition of TGF-β activity. (July 2017) - Orimoto, Ai; Kurokawa, Misaki; Handa, Keisuke; Ishikawa, Masaki; Nishida, Eisaku; Aino, Makoto; Mitani, Akio; Ogawa, Miho; Tsuji, Takashi; Saito, Masahiro
Highlights: F-spondin, as compared with periodontal ligament formation-related genes, is specifically expressed in the dental follicle. Using transgenic bioengineered tooth germ technology, f-spondin inhibits the expression of periodontal ligament-related genes. Recombinant f-spondin inhibits the expression of periostin, a marker of periodontal ligaments, though the inhibition of TGF-β activity. Abstract: Objective: F-spondin is an extracellular matrix (ECM) protein that belongs to the thrombospondin type I repeat superfamily and is a negative regulator of bone mass. We have previously shown that f-spondin is specifically expressed in the dental follicle (DF), which gives rise to the periodontal ligament (PDL) during the tooth root formation stage. To investigate the molecular mechanism of PDL formation, we investigated the function of f-spondin in DF differentiation. Design: The expression patterning of f-spondin in the developing tooth germ was compared with that of periodontal ligament-related genes, including runx2, type I collagen and periostin, by in situ hybridization analysis. To investigate the function of f-spondin during periodontal ligament formation, an f-spondin adenovirus was infected into the bell stage of the developing tooth germ, and the effect on dental differentiation was analyzed. Results: F-spondin was specifically expressed in the DF of the developing tooth germ; by contrast, type I collagen, runx2 and periostin were expressed in the DF and in the alveolar bone. F-spondin -overexpresssing tooth germ exhibited a reduction in gene expression of periostin and type I collagen in the DF. By contrast, the knockdown of f-spondin in primary DF cells increased the expression of these genes. Treatment with recombinant f-spondin protein functionally inhibited periostin expression induced by transforming growth factor-β (TGF-β). Conclusion: Our data indicated that f-spondin inhibits the differentiation of DF cells into periodontal ligament cells by inhibiting TGF-β. These data suggested that f-spondin negatively regulates PDL differentiation which may play an important role in the immature phenotype of DF.